PENGUATAN KAPASITAS MASYARAKAT DALAM PEMANFAATAN TEKNOLOGI DIGITAL SEBAGAI MEDIA EDUKASI KESEHATAN BERBASIS KOMUNITAS - Mahardika Ratih Resti Andani; Este Latifahanun (Jurnal Pengabdian Kepada Masyarakat Mulia Madani Yogyakarta, 2026)
Digital transformation has become a priority agenda for health development in Indonesia. The utilization of digital technology supports healthcare services but also opens up broader opportunities for disseminating health information and education to the public. Currently, the community has extensive access to digital devices, particularly smartphones. However, people primarily use these for communication and entertainment rather than as tools for health education. Therefore, we need community service activities that focus on strengthening the community's capacity to utilize digital technology as a medium for community-based health education. This community service activity was conducted in Sambirejo Village on Thursday, May 21, 2026, employing a participatory and community empowerment approach. The implementation process comprised several stages: preparation, socialization, training and practice, mentoring, and monitoring and evaluation. Overall, this activity successfully strengthened the community's capacity to use digital technology for community-based health education. The program's success was evidenced by the participants' active involvement and the establishment of health communication channels that can be utilized sustainably to support health promotion within the community.